The influence of capital risk, liquidity risk, and credit risk, on profitability with macroprudential intermediation ratio as a moderating variable - Febiyanni Febiyanni; Hermanto Hermanto (Institute of Computer Science (IOCS), 2023)
The banking industry faces bank business activities with increasingly complex risks due to rapid development that creates new risk exposures, so the bank must implement good risk management to reduce risks arising from bank activities. This study aims to determine the determinants of profitability, such as capital risk, liquidity risk, credit risk, and macroprudential intermediation ratio as moderation variables. This study utilized information taken from the financial statements of bank companies that have been registered on the IDX by using a purposive sampling test method that met the research criteria. The research period was taken for five years with a total of 130 data from 26 banking sector entities. This study utilized multiple linear analysis methods with secondary data types. The study results revealed a simultaneous influence between capital risk, liquidity risk, credit risk, and macroprudential intermediation ratios on profitability. Capital risk has a negative impact on profitability, liquidity risk shows a a positive relationship with profitability, and the presence of capital risk mediated by macroprudential intermediation ratios strengthens the relationship with profitability. Additionally, liquidity risk mediated by macroprudential intermediation ratios strenghthens the relationshio with profitability, while credit risk mediated by macroprudential intermediation ratios weakens the relationship with profitability.